Use of Artificial Intelligence (AI) Applications and Creative Behavior among Employees of the Education Department in Jeddah Governorate from their Perspective - Al-Jahni, Hoda Salah Musaed (Journal of Economic, Administrative and Legal Sciences, 2025)
This study aimed to evaluate using of Artificial Intelligence (AI) applications and the creative behavior of employees in the Education Department of Jeddah Governorate, focusing on decision-making applications, customer service applications, and human resource development applications. A descriptive survey approach was adopted, and a questionnaire was used as the primary data collection tool. The study population included all employees of the Education Department, and a convenience random sample of 994 employees responded electronically. Data were analyzed using the Statistical Package for the Social Sciences (SPSS). The results revealed a very high level of AI application usage, with customer communication applications ranking first (M = 4.22), followed by decision-making applications (M = 4.16), and human resource development applications (M = 4.02). The level of creative behavior among employees was also very high (M = 4.32). Based on these findings, the study recommends providing specialized training programs for employees on each application type, enhancing digital infrastructure to keep pace with rapid technological changes, increasing reliance on smart applications for big data analysis and predictive forecasting, and motivating employees while periodically assessing application effectiveness.